Analysis of Students' Ability to Use Simple Present Tense in Writing Descriptive Texts - Hanifa, Lika; Safitri, Loli (Journal of Educational Management and Strategy, 2024)
This research is about analyzing students' ability in using simple present tense in writing descriptive text in class X SMA N 1 Bonjol. The purpose of this study is to describe students' ability in using simple present tense in writing descriptive text in class X SMA N 1 Bonjol. This research used quantitative approach with purposive sampling technique. The respondents of this study were 30 students of class X SMA N 1 Bonjol. Data collection was done with a test to determine students' ability in using simple present tense in writing descriptive text. The results of this study show that the average score in making sentences using simple present tense in writing descriptive text is categorized as poor, with an average score of 24. This shows that students have not understood the use of simple present tense in writing descriptive text, especially in making sentences. The contribution of this study is to provide an overview of the difficulties faced by students in using simple present tense in descriptive text, which can be the basis for teachers to design more effective teaching strategies. Abstrak Penelitian ini tentang analisis kemampuan siswa dalam menggunakan simple present tense dalam menulis teks deskriptif di kelas X SMA N 1 Bonjol. Tujuan penelitian ini adalah untuk mendeskripsikan kemampuan siswa dalam menggunakan simple present tense dalam menulis teks deskriptif di kelas X SMA N 1 Bonjol. Penelitian ini menggunakan pendekatan kuantitatif dengan teknik purposive sampling. Responden penelitian ini adalah 30 siswa kelas X SMA N 1 Bonjol. Pengumpulan data dilakukan dengan tes untuk mengetahui kemampuan siswa dalam menggunakan simple present tense dalam menulis teks deskriptif. Hasil penelitian ini menunjukkan bahwa skor rata-rata dalam membuat kalimat menggunakan simple present tense dalam menulis teks deskriptif dikategorikan buruk, dengan nilai rata-rata 24. Ini menunjukkan bahwa siswa belum memahami penggunaan simple present tense dalam menulis teks deskriptif, terutama dalam membuat kalimat. Kontribusi penelitian ini adalah memberikan gambaran mengenai kesulitan yang dihadapi siswa dalam menggunakan simple present tense dalam teks deskriptif, yang dapat menjadi dasar bagi guru untuk merancang strategi pengajaran yang lebih efektif.